Malnutrition at Hospital Admission—Contributors and Effect on Length of Stay: A Prospective Cohort Study From the Canadian Malnutrition Task Force. (26th January 2015) - Allard, Johane P.; Keller, Heather; Jeejeebhoy, Khursheed N.; Laporte, Manon; Duerksen, Don R.; Gramlich, Leah; Payette, Helene; Bernier, Paule; Vesnaver, Elisabeth; Davidson, Bridget; Teterina, Anastasia; Lou, Wendy
Abstract : Background: In hospitals, length of stay (LOS) is a priority but it may be prolonged by malnutrition. This study seeks to determine the contributors to malnutrition at admission and evaluate its effect on LOS. Materials and Methods : This is a prospective cohort study conducted in 18 Canadian hospitals from July 2010 to February 2013 in patients ≥ 18 years admitted for ≥ 2 days. Excluded were those admitted directly to the intensive care unit; obstetric, psychiatry, or palliative wards; or medical day units. At admission, the main nutrition evaluation was subjective global assessment (SGA). Body mass index (BMI) and handgrip strength (HGS) were also performed to assess other aspects of nutrition. Additional information was collected from patients and charts review during hospitalization. Results : One thousand fifteen patients were enrolled: based on SGA, 45% (95% confidence interval [CI], 42%–48%) were malnourished, and based on BMI, 32% (95% CI, 29%–35%) were obese. Independent contributors to malnutrition at admission were Charlson comorbidity index > 2, having 3 diagnostic categories, relying on adult children for grocery shopping, and living alone. The median (range) LOS was 6 (1–117) days. After controlling for demographic, socioeconomic, and disease‐related factors and treatment, malnutrition at admission was independently associated with prolonged LOS (hazard ratio, 0.73; 95% CI, 0.62–0.86). Other nutrition‐related factors associated with prolonged LOS were lower HGS at admission, receiving nutrition support, and food intake < 50%. Obesity was not a predictor. Conclusion : Malnutrition at admission is prevalent and associated with prolonged LOS. Complex disease and age‐related social factors are contributors.